Manajemen Penerimaan Peserta Didik Baru (PPDB) Melalui Sistem Zonasi SDN Puncak 2 Kecamatan Cipanas Kabupaten Cianjur - Maman Suherman; Suharyanto H. Soro; Ani Nuraeni; Listia Rismayanti (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to analyze the effectiveness of the New Student Admission (PPDB) management in enhancing educational equity at SDN Puncak 2, Cipanas District, Cianjur Regency. This study employs a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. The primary focus of this research is on the strategies and policies implemented in the PPDB process, as well as their impact on access to and quality of education in the area. The results of the study indicate that the management of New Student Admission (PPDB) at SDN Puncak 2 has successfully enhanced educational equity through several strategic steps, such as the implementation of zoning policies, allocation of special quotas for underprivileged students, and transparency in the selection process. The implementation of the zoning policy has proven effective in reducing educational disparities between regions by ensuring that students from various backgrounds have equal opportunities to access quality primary education. Additionally, the provision of special quotas for students from low-income families offers them greater opportunities to receive a proper education. Overall, this study concludes that well-managed and fair New Student Admission (PPDB) can significantly contribute to improving educational equity. The recommendations provided include strengthening the zoning system, increasing public awareness of PPDB policies, and conducting periodic evaluations of PPDB implementation to ensure the sustainability and enhancement of education quality in the future.